RANCANG BANGUN APLIKASI PENJUALAN BUBUK KOPI ASLI SEMENDE BERBASIS ANDROID PADA UMKM IBU NURBAITI - Milia Rastiwi; Andi Christian; Khana Wijaya (STEKOM PRESS, 2023)
This research focuses on selling android-based coffee powder to disseminate semende specialty coffee. The purpose of this study is to design a sales application that has not been optimal so far and sales of cemente coffee powder have increased more than before. This is the background for this research. In collecting data, researchers used qualitative descriptive methods including conducting interviews, observation and literature study. So that data is obtained that there is no available access that makes it easy for UMKM Ms. Nurbaiti's to market this special cement coffee powder. The results of this study are in the form of an Android-based application design for the sale of original cement coffee powder for UMKM Ms. Nurbaiti's s which is expected to help with the problems that occur. Using an Android-based sales information system can help UMKM owners and buyers sell and buy coffee powder quickly, for the system development method using the RAD (Rapid Application Development) method.